Shallow Overpressure Formation in the Deep Water Area of the Qiongdongnan Basin, China - Ren, Jinfeng; Xu, Litao; Shi, Wanzhong; Yang, Wei; Wang, Ren; He, Yulin; Du, Hao (Frontiers in Earth Science, 2022)
The scarcity of drilling in the deep water area of Qiongdongnan Basin restricts the cognition and prediction of overpressure. In this paper, a shallow zone of overpressure at the depth of 900-1200 m below the sea floor in the deep water area was found by analyzing electronic logs, mud pressure (Mud pressure is a product of the height of the column of mud, density and gravity acceleration) and test pressure from DST and MDT, and the interpretation of anomalous seismic interval velocities. The shallow overpressure is a newly observed geological phenomenon in the South China Sea for which the generation mechanisms are not well understood, despite similar observations and analyses elsewhere in the world. Two representative wells, one each located in the shallow water and the deep water areas, respectively were selected to investigate the vertical distribution of the shallow overpressure. The top of the overpressure in Well A in the shallow water area is about 2111 m below sea floor, while the top of the overpressure in Well B in the deep water area is about 1077 m below sea floor. A pressure coefficient (i.e., ratio of pore pressure to the normal hydrostatic pressure measured from the sea surface) profile was constructed from the shallow water area to the deep water area using the calibrated relationship between seismic interval velocities and pressure data from 30 wells. The distance between the top of the overpressure and the seabed is predicted to be between 900-1200 m in the deep water area Basin. Disequilibrium compaction is the interpreted primary cause of the shallow overpressure and the results of basin modeling indicate that the shallow overpressure was generated since 5.5Ma.